(untitled) (London Journal of Medical and Health Research, 2025)
Background: Multiple Myeloma, a haematological malignancy that is characterized by the clonal proliferation of plasma cells often presents with renal dysfunction, anaemia and bone lesions (CRAB criteria). Diagnosing Multiple Myeloma in patients who are suffering from preexisting chronic kidney disease and other comorbidities such as Diabetes and Hypertension can be quite challenging as these diseases have overlapping clinical presentation. This case serves to highlight the complexities in diagnosing MM in a patient with well-controlled comorbid diseases and atypical renal presentation. The Case: We describe a case of a 66-year-old female patient with chronic kidney disease stage 2, diabetes mellitus type 2, chronic hypertension and coronary heart disease that presented to the clinic with complaints of lower limb oedema and severe proteinuria. Laboratory findings revealed a hypochromic normocytic anaemia and increased ESR. Initially, it was suspected to be diabetic nephropathy but the patient’s optimal glycaemic control as well as the disproportionate levels of anaemia and proteinuria cast doubts on that diagnosis. A sternal puncture was performed and revealed Multiple Myeloma. Conclusion: Physicians must consider multiple myeloma as a part of a differential diagnosis in patients with chronic kidney disease presenting with atypical haematological or renal signs, particularly those that have a multitude of comorbidities. Such clinical suspicion may lead to early diagnosis, thus greatly reducing mortality rates in this patient category. This case also serves to highlight the importance of utilising a multidisciplinary approach in patients with overlapping comorbid conditions.